2019
DOI: 10.1111/aji.13108
|View full text |Cite
|
Sign up to set email alerts
|

Meconium‐stained amniotic fluid exposure is associated with a lower incidence of offspring long‐term infectious morbidity

Abstract: Objective Meconium‐stained amniotic fluid (MSAF) is a well‐established risk factor for immediate adverse neonatal outcomes and was recently suggested to be associated with microbial invasion of the amniotic cavity. We aimed to determine whether MSAF exposure during labor carries a longer lasting impact on pediatric infectious morbidity. Study design A population‐based cohort analysis was performed including all singleton deliveries occurring between 1991 and 2014 at a single tertiary medical center. Exposure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…The simple theory of microorganism contamination leading to GE has been recently transformed. Recent studies have shown that GE develops as a result of a combination of complex interactions between the individual's genetic background, alterations in the composition of the intestinal microbiota, a dysregulated innate and adaptive immune system, environmental factors and microorganism contamination …”
Section: Discussionmentioning
confidence: 99%
“…The simple theory of microorganism contamination leading to GE has been recently transformed. Recent studies have shown that GE develops as a result of a combination of complex interactions between the individual's genetic background, alterations in the composition of the intestinal microbiota, a dysregulated innate and adaptive immune system, environmental factors and microorganism contamination …”
Section: Discussionmentioning
confidence: 99%
“…Meconium-stained amniotic fluid (MSAF) is a condition in which infants have passed meconium in amniotic fluid. The incidence of MSAF is generally about 5%-20% of all births [1][2][3] and increases with advanced gestational age. 4 5 MSAF can be a sign of fetal maturity or of a pathological condition, such as an infant with hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies associated maternal inflammatory statuses with offspring with long-term alterations of immune responses that result in childhood infectious morbidity. These maternal conditions were pure infectious diseases [19,30,31], but were also attributed to conditions such as obesity and smoking that may involve maternal subclinical inflammation [20,21,[32][33][34]. This association between intrauterine inflammation and childhood morbidity, however, showed mixed trends in different studies.…”
Section: Long-term Outcomes Of Offspring Born To Women With Tuberculosismentioning
confidence: 99%
“…Melville et al demonstrated that infants exposed to intrauterine inflammation show increased immune maturation and require less intensive and respiratory care after birth [20]. Likewise, exposure to meconium-stained amniotic fluid was associated with lower incidence of long-term infectious morbidity of the offspring [21]. In contrast, other studies showed increased risk of short and long-term infectious morbidity in children born to mothers with an augmented inflammatory state during pregnancy.…”
Section: Long-term Outcomes Of Offspring Born To Women With Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation